Flouting Maxim Types Found in “Thor Ragnarok” Movie - Rei Shifa Devi; Ambalegin Ambalegin (LPPM Universitas Bumigora Mataram, 2022)
The focus of this research is the flouting of maxim purposed by Grice (1975) theory of cooperative principle. This focus concerned on the types of flouting maxim with pragmatic as the approach. In doing the flouting the participants conciously or unconciously tend to break the principles and unfulfill the rules in cooperative principle. The purpose of this research was to find out about the types of flouting maxim in the movie. This research used the movie directed by Taika Waititi named “Thor Ragnarok”. This study used qualitative research by Creswell (2013) in collecting the data. The observational method and the non-participatory technique by (Sudaryanto, 2015) was used to collect the data. The pragmatic identity method was used to analyze the data, and the pragmatic competence-in-equalizing technique was used as the research technique. The result of this study revealed that there were 17 data related to the flouting maxims. The frequent type found was the flouting of maxim quantity. As the character tend to give information or contribution as required. The second type found was the flouting of maxim quality with 4 times occurances, where the characters in the movie tend to say something opposite from the factual event. The flouting maxim of relation with 2 times appeareance. And lastly, the flout of maxim manner appeared 3 times in the movie